F: Pengaruh Pelatihan Supervisi Klinik Kepada Kepala Ruang Terhadap Persepsi Pengetahuan dan Kepatuhan Perawat Tentang Model Safewards di RS X dan Y - Junita Lasma; Emiliana Tarigan; Bantari Wisynu Kusuma Wardhani; Neng Esti Winahayu (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
ABSTRACT Nurses are among the healthcare professionals who interact most frequently with patients in improving healthcare service quality, particularly in implementing the Safewards model. Therefore, optimization through clinical supervision is needed. This study aimed to analyze the effect of clinical supervision training for head nurses on staff nurses’ perceived knowledge and compliance regarding the Safewards model at Hospital X and Y. This study used a quasi-experimental design with pre-post tests in intervention and control groups. The study was conducted from January 10 to February 19, 2026. Clinical supervision training was provided to 12 head nurses, while clinical supervision implementation involved 60 staff nurses. Standardized questionnaires were used to measure perceived knowledge and compliance. The results showed that most respondents were Diploma III nursing graduates with more than 15 years of work experience and categorized as PK III. There was an increase in head nurses’ knowledge regarding clinical supervision after training, as well as improvements in staff nurses’ perceived knowledge and compliance regarding the Safewards model after clinical supervision. Significant differences were found in perceived knowledge (p-value = 0.009) and compliance (p-value = 0.005) before and after the intervention. Clinical supervision training for head nurses significantly influenced perceived knowledge and compliance (p-value = 0.001). The training contributed 14.4% to perceived knowledge and 23.6% to perceived compliance. Hospitals are expected to implement structured and sustainable clinical supervision training programs and integrate training-based learning mechanisms into Safewards implementation SOPs.Keywords: safewards model; clinical supervision; perceived knowledge; nurse compliance; head nurse training